A novel application of a surface ElectroMyoGraphy-based control strategy for a hand exoskeleton system: A single-case study. (13th February 2019) - Secciani, Nicola; Bianchi, Matteo; Meli, Enrico; Volpe, Yary; Ridolfi, Alessandro
Robotics is increasingly involving many aspects of daily life and robotic-based assistance to physically impaired people is considered one of the most promising application of this largely investigated technology. However, the World Health Organization reports that, so far, only 10% of people in need can get access to the so-called assistive technology also due to its high costs. This work aims to tackle the aforementioned point presenting an innovative control strategy for a low-cost hand exoskeleton system based on surface electromyography signals. Most of the activities of daily living are, in fact, carried out thanks to the hands while the exploitation of surface electromyography signals represents a non-invasive technique in straightforwardly controlling wearable devices. Although such approach results deeply studied in literature, it has not been deeply tested on real patients yet. The main contribution of this article is hence not only to describe a novel control strategy but also to provide a detailed explanation of its implementation into a real device, ready to be used. Finally, the authors have evaluated and preliminary tested the proposed technique enrolling a patient in a single-case study.